EP.FRI.390 Improving care for patients with acute bowel obstruction: A closed loop audit. (28th October 2021) - Clayphan, Benjamin; Fairclough, Anna; Lim, Jeff; Alexander, Roderick
Abstract: Aims: Acute Bowel Obstruction (ABO) accounts for 10% of emergency surgical admissions and when surgery is required mortality can exceed 10%. Early diagnosis is associated with improved patient outcomes and timely acquisition of abdominal CT scans can help prevent delays. The NCEPOD 2020 report on ABO identified 'delays in imaging' as a key area for improvement in the care of these patients, with these delays being exacerbated if an abdominal X-ray (AXR) was performed as well as an abdominal CT. This study looks at ways to expedite the diagnosis of patients presenting with ABO. Methods: A retrospective audit of 77 patients admitted from A&E or SAU with ABO from April 2019 to February 2020 was conducted. Imaging modality, time-to-CT scan and time-to-diagnosis was recorded. Results and recommendations were presented locally and an evidence based ABO care pathway was implemented and publicised. 20 patients were audited prospectively, post care pathway implementation. Results: 70.1% of patients from the initial audit received a CT-scan and 42% of these patients received an AXR before their eventual CT-scan. The average wait for a definitive radiological diagnosis was 27.8hr. After implementation of the pathway only 18% of patients audited received both modes of imaging and the average time to diagnosis has been reduced to 10.7hr. Conclusions: Raising awareness of the appropriate and timely use of CT-scans in the diagnosis of ABO has reduced the number of concomitant AXR for these patients, expediting the making of a definitive diagnosis and improving patient outcomes.